TRIM11 promotes breast cancer cell proliferation by stabilizing estrogen receptor α - Jianing Tang (Neoplasia: An International Journal for Oncology Research, 2020)
Breast cancer is the most commonly diagnosed malignancy in female worldwide, over 70% of which are estrogen receptor α (ERα) positive. ERα has a crucial role in the initiation and progression of breast cancer and is an indicator of endocrine therapy, while endocrine resistance is an urgent problem in ER-positive breast cancer patients. In the present study, we identify a novel E3 ubiquitin ligase TRIM11 function to facilitate ERα signaling. TRIM11 is overexpressed in human breast cancer, and associates with poor prognosis. The protein level of TRIM11 is highly correlated with ERα. RNA-seq results suggest that ERα signaling may be an underlying target of TRIM11. Depletion of TRIM11 in breast cancer cells significantly decreases cell proliferation and migration. And the suppression effects can be reversed by overexpressing ERα. In addition, ERα protein level, ERα target genes expression and estrogen response element activity are also dramatically decreased by TRIM11 depletion. Further mechanistic analysis indicates that the RING domain of TRIM11 interacted with the N terminal of ERα in the cytoplasm and promotes its mono-ubiquitination, thus enhances ERα protein stability. Our study describes TRIM11 as a modulating factor of ERα and increases ERα stability via mono-ubiquitination. TRIM11 could be a promising therapeutic target for breast cancer treatment.